Джерела з історії сискної поліції у Волинській губернії (1908-1917рр.) - Яцишин, М.; Yatsyshyn, М. (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті проаналізовано історіографічну та джерельну базу з історії становлення та функціонування сискної поліції в Україні, й у Волинській губернії зокрема. Головним завданням сискних наглядачів та сищиків залишалось стеження за кримінальним елементом у великих містах, де відбувалася концентрація закладів з підвищеною криміногенною привабливістю. Визначальний вплив на організаційні форми сискної поліції, обсяг компетенції, основні напрями діяльності, місце та роль в державному механізмі чинили процеси суспільно-економічного і політичного розвитку, які відбувалися в державі в той чи інший історичний період. The article considers historiography and source base on the history of the formation and functioning of the detective police in Ukraine, and in Volyn Province, in particular. The analysis of the source base shows that in the writings of pre-revolutionary authors the problem of detective police of the Russian Empire as a whole, as well as the issues of the regional detective departments, is under-investigated. Their works highlighted only certain aspects of the organization and activities of the criminal system, but few attempts have been made to elucidate organizational and legal foundations of the detective police activities of the Russian Empire. The criminogenic situation in Volyn, in comparison with other regions of Ukraine, had always been under the control of the tsarist government and did not provoke its anxiety. The in-depth study of the sources has revealed that in Volyn there was no sustainable criminal environment that required operational covert surveillance. Inherent to our region home crimes did not require special attraction of undercover agents because there were no such crimes, in which secret surveillance ought to be provided. The main task of the detectives was to monitor or spy the criminal element in large cities with their concentration of institutions with increased criminogenic activity.
Source Base on the History of the Detective Police Force in the Volyn Province (1908-1917)
Keywords: Волинська губернія; Російська імперія; сискна поліція; сискні відділення; повітове поліцейське управління; Volyn Province; Russian Empire; detective police; detective department; District (Povit) Police Department